Makna Simbolik pada Prosesi Makkuwaélawi di Desa Mattaropurae Kabupaten Bone - Rara Assahra; Andi Fatimah Yunus; Aswati Asri (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. The purpose of this study was to identify objects and food and to reveal the symbolic meaning of makkuwaélawi ‘akikah’ in the Bugis community in Mattaropurae, Bone Regency based on Charles Sanders Peirce’s semiotic theory. This study uses a qualitative descriptive approach to data analysis techniques obtained through observation, interviews and documentation. The results of the study show that objects and food are found in the makkuwaelawi tradition, namely icons (1) Sokko surrounded by incense which is made high and above means elevating the status of Mappakuwaélawi people, (2) Manu kampong (free-range chicken). objects and food contained in the makkuwaelawi tradition, namely index (1) Pakdupa (incense), (2) Maccemme ana’ lolo (bathe the baby). Objects and food contained in the makkuwaelawi tradition are symbols (1) utti nisi' (plantain), (2) Kaluku lolo (young coconut), (3) Sokko pute (white sticky rice) and sokko lotong (black sticky rice), (4) Were 'na liling (rice and candles). symbolic meaning can be obtained a clear picture of meaning that the Bugis people in Mattaropurae Bone district interpret objects and food in makkuwaélawi 'akikah' as a symbol of protection, welfare, happiness and sustenance because they are expected when children it's great can be useful for everyone. Keywords: objects and food, symbolic meaning of makkuwaélawi